Be diligent: Discover the joy of serving others as you walk with the master servant - Wiersbe, Warren W.; (1929-2019) (United Stated of America, 1987)
Christianity is not a passive faith. It is a dynamic, proactive way of life where God's love motivates us to ministry, to help those in need, and to serve those around us. And no one better illustrates this lifestyle than our Savior. The gospel of Mark shares the life, love, and ministry of Christ, who provides the ultimate example for those longing to actively serve others and God. Part of Dr. Warren W. Wiersbe's best-selling BE commentary series, Be Diligent has study questions and an introduction by Ken Baugh. A respected pastor and teacher, Dr. Wiersbe encourages us to be diligent in kingdom work. You'll be inspired to pursue a lifestyle of service, deepen your ministry, and put feet to your faith.
Keywords: Bible -- Mark -- Commentaries